2000
DOI: 10.1002/1097-0282(2000)57:6<329::aid-bip20>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

IR spectroscopic characteristics of cell cycle and cell death probed by synchrotron radiation based Fourier transform IR spectromicroscopy

Abstract: Synchrotron radiation based Fourier transform IR (SR‐FTIR) spectromicroscopy allows the study of individual living cells with a high signal to noise ratio. Here we report the use of the SR‐FTIR technique to investigate changes in IR spectral features from individual human lung fibroblast (IMR‐90) cells in vitro at different points in their cell cycle. Clear changes are observed in the spectral regions corresponding to proteins, DNA, and RNA as a cell changes from the G1‐phase to the S‐phase and finally into mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
145
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(158 citation statements)
references
References 19 publications
12
145
1
Order By: Relevance
“…Absorptions in this spectral region arise from the carbonyl C ¼ O stretching mode of phospholipids. 27,28 It has been described that upon washing with ethanol, phospholipids together with other membrane lipids are removed from the sample and thus their intensity decreases in the spectrum. 15 This corroborates the changes observed above for the CH 2 modes.…”
Section: Discussionmentioning
confidence: 99%
“…Absorptions in this spectral region arise from the carbonyl C ¼ O stretching mode of phospholipids. 27,28 It has been described that upon washing with ethanol, phospholipids together with other membrane lipids are removed from the sample and thus their intensity decreases in the spectrum. 15 This corroborates the changes observed above for the CH 2 modes.…”
Section: Discussionmentioning
confidence: 99%
“…At present Fourier Transform Infrared Microspectrosopy (FTIRM) and Confocal Raman Microspectroscopy (CRM) have identified in-situ molecular alterations associated with cell death via apoptosis [1][2][3] or necrosis [4,5], or as a result of proliferative changes in cellular activity [6][7][8] or mitosis [9]. It has also been shown that these modalities can identify molecular changes associated with changes in the phenotype of differentiating embryonic cells [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the important considerations already highlighted for IR spectroscopy were also highlighted in this study, particularly the importance of performing Mie scattering correction. Significant differences in Mie scattering contribution between the different cell cycle stages were observed, likely due to changes in amount of cellular content [65], and therefore the RMieS-EMSC correction algorithm [40] was used. The ability to detect changes after 24 hr treatment was highlighted as an advantage with respect to HTS, and the benefit of distinguishing cell cycle without additional staining was confirmed as an ideal next step.…”
Section: Infrared Spectroscopy For Monitoring Drug-cell Interactionmentioning
confidence: 99%